2021
DOI: 10.1016/j.cemconcomp.2020.103823
|View full text |Cite
|
Sign up to set email alerts
|

Chloride-initiated corrosion in alkali activated reinforced concrete

Abstract: The use of ordinary Portland cement (PC) as the principal binder in concrete brings with it significant environmental challenges through the consumption of fossil fuels and emission of carbon dioxide (CO 2 ) during cement production. Concrete specimens made with an alkali activated cementitious material (AACM) produced from an alternative binder and conventional Portland cement concrete were exposed to corrosion inducing environments for 1 750 days to monitor their relative durability. AACM concrete shows high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Moreover, one of the more likely formed phases is actually an amorphous gel with a highly variable stoichiometry, mainly depending on mix design, thus on the initial materials. An upward trend of shrinkage is generally observed with the increase of the amount of activators in the formulation [39]. RB and CB have been thereby shown earlier to be active additives, i.e., activators.…”
Section: ) Physical Properties and Compressive Strengthmentioning
confidence: 89%
“…Moreover, one of the more likely formed phases is actually an amorphous gel with a highly variable stoichiometry, mainly depending on mix design, thus on the initial materials. An upward trend of shrinkage is generally observed with the increase of the amount of activators in the formulation [39]. RB and CB have been thereby shown earlier to be active additives, i.e., activators.…”
Section: ) Physical Properties and Compressive Strengthmentioning
confidence: 89%
“…In PC concrete, alkalinity is buffered by portlandite (Ca(OH) 2 ) and increased further by the concentration of additional alkalis (e.g., Na + and K + ). However, for AAC, the alkalinity of the pore solution depends on the alkali dosage and silicate modulus used in the activating solution, and there can be variations between high and low calcium AAMs (Mangat et al 2021). To calculate the alkalinity of the pore solution in AACs, the composition of the activating solution, mineralogical composition of the precursors, and free water content, were used as inputs in GEM-Selektor.…”
Section: Chloride Thresholdmentioning
confidence: 99%
“…The high pH in AAMs creates a hydroxide concentration gradient between the inner material and the external environment, resulting in leaching of hydroxide (and alkali) ions. Research conducted by Mangat et al (2021) demonstrated that in a high calcium AAM concrete, the hydroxyl ion concentration reduced from 0.155 to 0.017 mol/L between 180 and 1750 days at a cover depth of 10 mm. In comparison, the OHconcentration in PC concrete ranged from 0.014 to 0.009 mol/L under an accelerated corrosive environment with multiple wetting and drying cycles within the same time frame of 1750 days.…”
Section: Chloride Thresholdmentioning
confidence: 99%
“…This interface is related to the double action of sulphide content in AAMs that consumes oxygen at the steel-mortar interface and reacted with sulphide products on the steel interface [88], which inhibits the formation of the passive layer. Mangat et al [89] investigated the durability of AAS concrete and OPC concrete under the aggressive environment for up to 1750 days; they found the SO 2− 3 content at the steel-AAS concrete interface is up to 80% higher than OPC concrete. However, the corrosion resistance mechanism of this sulphide film on the steel surface remains unclear.…”
Section: Steel-aam Concrete Interfacementioning
confidence: 99%